A RESEARCH ON FEARS OF CORONAVIRUS AMONG PEOPLE IN SPORTS SCIENCE - Osmanoğlu, Hasan; Uzun, Meliha; Güney, Gamze; Adıgüzel, Serdar (ANADOLU UNIV, 2022)
The people of the world have faced and struggled with pandemics on several occasions from the past to the present. Today, the world has most recently faced the COVID-19 pandemic. The pandemic broke out on December 31, 2019, in Wuhan City, China. The WHO declared COVID-19 as a pandemic since it changed into a global pandemic, spreading rapidly to more than one country and causing an acute contagious pandemic. Likewise, it soon broke out in Turkey. Although many measures were taken to prevent the spread of the virus, its spreading speed continued to increase without interruption. As part of the measures, primary education, secondary education, high schools, and universities were suspended and the online education system was launched. In this context, this study reports on fears of COVID-19 among individuals in the field of sports sciences in terms of different variables. The paper consists of a total of 403 volunteers (f: 38 and m: 265), living in Şırnak province. The COVID-19 Phobia Scale (CP19-SE) was used as a data collection tool in the study. In the analysis of data, descriptive statistical methods, t-test, One-Way Analysis of Variance (ANOVA), and Gabriel Post-Hoc Test were used. It was concluded that the scores of the psychological, somatic, and social sub-scales of the CP19-SE and the total score showed a statistically significant difference according to the gender variable, but the score of the economic sub-scale did not make a significant difference according to gender. In addition, the somatic and economic subscales of the COVID-19 Phobia Scale and the total coronavirus scores showed a statistically significant difference according to the age variable. However, the CP19-SE did not show a statistically significant difference according to marital status, COVID-19 contraction, and department. It was found that the variables of gender, age, and employment status had an effect on the levels of COVID-19 phobia and that individuals were generally affected psychologically, somatically, socially, and economically in the context of COVID-19 phobia.
Keywords: Sports; Covid-19; Phobia; Pandemic